Pengaruh Review Produk, Kenyamanan, Kepercayaan Konsumen dan Harga Terhadap Keputusan Pembelian di Lazada Market Place Medan - Demak Claudia Yosephine Simanjuntak; Ivine Rivio; Fransiscus Daniel Silaholo (Management Studies and Entrepreneurship Journal (MSEJ), 2022)
When consumers already to constantly has decisions about which products to buy, these decisions are often uncertain because the consumer feels a certain risk of degree in making a purchase decision. The decision to purchase over the internet is indicated by an uncertainty or risk that requires confidence to be expressed, which will reduce the perception of risk to arrive at a purchase decision. This study is based on Google research at Lazada Market Place in Medan City. The tentative period for this study is from August to March 2022. The methodology used in this study is the existence of MSME entrepreneurs in the commercial business sector in the Medan Petisah area. This study was conducted in Medan Petisah District, City of Medan. This study used quantitative data because the data presented is related to numbers. Quantitative research are emphasizes testing theory through measuring research variables with numbers and analyzing data using statistical procedures .Coefficient regression for the independent variable price is 0.760 and is positive, this means that every 1 unit increase in the price of the independent variable will increase the dependent variable''s buying decision by 0.760 units with the assuming other variables already fixed. Based on the results of the t-test, the working capital turnover variable has a significant and negative influence on profitability (ROI) in manufacturing companies in the year 2015-2017, 5. The effect of all independent variables on the dependent variable is expressed as an adjusted R-squared value of 0.175 or 17.5%. And another 82.5% is explained by foreign factors not observed in this study. Keywords: Purchase Decision, MSME Enterpreneurs, t-test